(untitled) (American Journal of Management, 2023)
This paper explores the concept of branding and introduces the Brand Evolution Process (BEP) as a comprehensive framework for marketing education. Branding, a pivotal aspect of marketing, has evolved over time and remains critical in today’s dynamic business environment. The BEP consists of three stages: Brand Development, Brand Management, and Brand Optimization. It offers a structured approach to understanding how brands are created, managed, and adapted over time. The study emphasizes the importance of brand evolution in marketing and education. Brand Development involves defining the brand’s identity, attributes, and positioning, while Brand Management focuses on maintaining and leveraging brand equity. Brand Optimization examines strategies like extensions and repositioning. By organizing these concepts into a cohesive framework, the BEP serves as a valuable tool for marketing educators. Future research may measure the effects of incorporating the BEP into the curriculum and its alignment with employer expectations. This paper underscores the holistic nature of branding and its significance in contemporary marketing education, providing a foundation for the development of future brand managers.